Prevalence and characterization of carbapenem‐resistant bacteria in water bodies in the Los Angeles–Southern California area - Dana E. Harmon; Osvaldo A. Miranda; Ashley McCarley; Michelle Eshaghian; Natasha Carlson; Cristian Ruiz (MicrobiologyOpen, 2019)
Abstract Carbapenems are β‐lactam antibiotics used in healthcare settings as last resort drugs to treat infections caused by antibiotic‐resistant bacteria. Carbapenem‐resistant bacteria are increasingly being isolated from healthcare facilities; however, little is known about their distribution or prevalence in the environment, especially in the United States, where their distribution in water environments from the West Coast has not been studied before. The aim of this study was to determine the prevalence of carbapenem‐resistant bacteria and carbapenemase genes in water bodies from the Los Angeles area (California, USA). All samples that were analyzed contained carbapenem‐resistant bacteria with a frequency of between 0.1 and 324 carbapenem‐resistant cfu per 100 mls of water. We identified 76 carbapenem‐resistant or ‐intermediate isolates, most of which were also resistant to noncarbapenem antibiotics, as different strains of Enterobacter asburiae, Aeromonas veronii, Cupriavidus gilardii, Pseudomonas, and Stenotrophomonas species. Of them, 52 isolates were carbapenemase‐producers. Furthermore, PCR and sequence analysis to identify the carbapenemase gene of these carbapenemase‐producing isolates revealed that all Enterobacter asburiae isolates had a blaIMI‐2 gene 100% identical to the reference sequence, and all Stenotrophomonas maltophlia isolates had a blaL1 gene 83%–99% identical to the reference blaL1. Our findings indicate that water environments in Southern California are an important reservoir of bacteria‐resistant to carbapenems and other antibiotics, including bacteria carrying intrinsic and acquired carbapenemase genes.